Transduced PEP-1-PON1 proteins regulate microglial activation and dopaminergic neuronal death in a Parkinson's disease model. (September 2015) - Kim, Mi Jin; Park, Meeyoung; Kim, Dae Won; Shin, Min Jea; Son, Ora; Jo, Hyo Sang; Yeo, Hyeon Ji; Cho, Su Bin; Park, Jung Hwan; Lee, Chi Hern; Kim, Duk-Soo; Kwon, Oh-Shin; et al.
Abstract: Parkinson's disease (PD) is an oxidative stress-mediated neurodegenerative disorder caused by selective dopaminergic neuronal death in the midbrain substantia nigra. Paraoxonase 1 (PON1) is a potent inhibitor of low-density lipoprotein (LDL) and high-density lipoprotein (HDL) against oxidation by destroying biologically active phospholipids with potential protective effects against oxidative stress-induced inflammatory disorders. In a previous study, we constructed protein transduction domain (PTD) fusion PEP-1-PON1 protein to transduce PON1 into cells and tissue. In this study, we examined the role of transduced PEP-1-PON1 protein in repressing oxidative stress-mediated inflammatory response in microglial BV2 cells after exposure to lipopolysaccharide (LPS). Moreover, we identified the functions of transduced PEP-1-PON1 proteins which include, mitigating mitochondrial damage, decreasing reactive oxidative species (ROS) production, matrix metalloproteinase-9 (MMP-9) expression and protecting against 1-methyl-4-phenylpyridinium (MPP + )-induced neurotoxicity in SH-SY5Y cells. Furthermore, transduced PEP-1-PON1 protein reduced MMP-9 expression and protected against dopaminergic neuronal cell death in a 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced PD mice model. Taken together, these results suggest a promising therapeutic application of PEP-1-PON1 proteins against PD and other inflammation and oxidative stress-related neuronal diseases. Highlights: PEP-1-PON1 transduces into BV2, SH-SY5Y cells and animal brains. PEP-1-PON1 protects against LPS exposed BV2 cell death. PEP-1-PON1 protects against MPP + -induced neurotoxicity in SH-SY5Y cells. PEP-1-PON1 protects against dopaminergic neuronal cell death in a MPTP-induced PD mice. PEP-1-PON1 can be a therapeutic agent for inflammation and oxidative stress-related neuronal diseases.